Aroma Loss in Rice as Affected by Various Conditions during Postharvest Operations - Baradi, Mary Ann U. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2012)
The effect of various conditions during drying, storage and milling on the aroma level and concentrations of the principal aroma compound 2-acetyl-1-pyrroline (2AP) of the Philippine aromatic rice Maligaya Special 6 (MS 6) was investigated. Sensory evaluation revealed no significant variations in the aroma of the raw and cooked milled rice samples obtained from the different drying air temperatures (35, 45 and 55 °C) and storage temperatures (ambient at 27, 15 °C). However, the aroma levels of the milled rice samples were higher (65% recovery) than those of the brown rice samples (75% recovery). There were also no significant variations in the 2AP concentrations determined through gas chromatography-flame ionization detector among the rice samples obtained from the various drying air and storage temperatures, and milling degree. Cold storage did not significantly minimize the loss of aroma in rice. The amount of 2AP in rice, however, decreased with storage time. There was a rapid loss of 2AP during the first 5 wk but later slowed down until it did not change any further, indicating the presence of starch-bound 2AP. Around 63–67% of the total 2AP was lost in brown and milled rice of MS 6 paddy kept at ambient. Semi-empirical equations were also developed to describe the loss of aroma as affected by temperature and time.